2011
DOI: 10.1007/s00467-010-1744-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of pediatric patients with lower urinary tract dysfunction and their caregivers

Abstract: The interest in quality of life (QoL) studies has increased as they are useful instruments to evaluate and compare medical care delivery and the impact of health interventions. The perception of QoL differs among individuals. Its characterization is especially difficult in the pediatric age group as each developmental stage presents specific demands. The prevalence of congenital lower urinary dysfunction is high and their management changes the daily routine of the patients and their families. In a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
0
15
0
8
Order By: Relevance
“…Therefore their parents must be adequately oriented regarding the need for a psychological approach [33]. Also, evaluation of quality of life of children and adolescents with LUTD found that such children share positive perceptions toward their family life and their playtime but tend to develop an introspective behavior in relation to their peers because they fear discrimination that may result from exposure of their dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore their parents must be adequately oriented regarding the need for a psychological approach [33]. Also, evaluation of quality of life of children and adolescents with LUTD found that such children share positive perceptions toward their family life and their playtime but tend to develop an introspective behavior in relation to their peers because they fear discrimination that may result from exposure of their dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…31 In other studies, children with sickle cell disease, spinabifida,Duchenne muscular dystrophy (DMD), bladder exstrophy, lower urinary tract dysfunction, and congenital hearing impairment reported impaired QoL compared with the general population or age-matched control children (Table 2). 29,32,[41][42][43][44] Perceived QoL in boys with DMD measured by using PedsQL was lower for all domains, except for the emotional domain, compared with unaffected age-matched control subjects. 32 However, for boys aged ,10 years, QoL for social, emotional, or school domains was comparable to control subjects.…”
Section: Studies Of Self-reported Qolmentioning
confidence: 96%
“…Due to small number of patients, most studies could not draw any conclusion about the impact of individual comorbidities. However, in particular, comorbidities that tend to represent an obstacle to social activities, such as urological malformations leading to urinary incontinence and the necessity of undergoing catheterization, may be prone to negatively affect HRQoL [37, 38]. …”
Section: Important Determinants Of Hrqol and Proposed Interventionsmentioning
confidence: 99%